2009
DOI: 10.1590/s1516-89132009000400016
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation and in vitro conservation of Neoglaziovia variegata (Arr. Cam.) mez, a fiber producing bromeliad from Brazil

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 18 publications
3
15
0
7
Order By: Relevance
“…In the case of A. distichantha, although germination also began on the fifth day after sowing, the process went on until the 35 th and 40 th day for seeds kept under light and darkness, respectively. Silveira et al (2009), working with Neoglaziovia variegate in the same light conditions we report here, also observed differences in germination rate when studying seeds collected in ripe and immature fruits. These authors reported that germination was favored by light, observing 100% and 80% of radicle protrusion at the 10 th and 15 th days for mature and immature seeds, respectively.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…In the case of A. distichantha, although germination also began on the fifth day after sowing, the process went on until the 35 th and 40 th day for seeds kept under light and darkness, respectively. Silveira et al (2009), working with Neoglaziovia variegate in the same light conditions we report here, also observed differences in germination rate when studying seeds collected in ripe and immature fruits. These authors reported that germination was favored by light, observing 100% and 80% of radicle protrusion at the 10 th and 15 th days for mature and immature seeds, respectively.…”
Section: Resultssupporting
confidence: 77%
“…Most protocols which use seeds as explant source in bromeliads (Pickens et al, 2006;Bellintani et al, 2008;Silveira et al, 2009;Souza et al, 2009) do not report contamination.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations